A bibliometric analysis of COVID-19 publications in neurology by using the visual mapping method - Zhang, Qian; Li, Jian; Weng, Ling (Frontiers in Public Health, 2022)
Background The characteristic symptom of coronavirus disease 2019 (COVID-19) is respiratory distress, but neurological symptoms are the most frequent extra-pulmonary symptoms. This study aims to explore the current status and hot topics of neurology-related research on COVID-19 using bibliometric analysis. Methods Publications regarding neurology and COVID-19 were retrieved from the Web of Science Core Collection (WoSCC) on March 28 2022. The Advanced search was conducted using “TS = (‘COVID 19’ or ‘Novel Coronavirus 2019’ or ‘Coronavirus disease 2019’ or ‘2019-nCOV’ or ‘SARS-CoV-2’ or ‘coronavirus-2’) and TS = (‘neurology’or ‘neurological’ or ‘nervous system’ or ‘neurodegenerative disease’ or ‘brain’ or ‘cerebra’ or ‘nerve’)”. Microsoft Excel 2010 and VOSviewer were used to characterize the largest contributors, including the authors, journals, institutions, and countries. The hot topics and knowledge network were analyzed by CiteSpace and VOSviewer. Results A total of 5,329 publications between 2020 and 2022 were retrieved. The United States, Italy, and the United Kingdom were three key contributors to this field. Harvard Medical School, the Tehran University of Medical Sciences, and the UCL Queen Square Institute of Neurology were the major institutions with the largest publications. Josef Finsterer from the University of São Paulo (Austria) was the most prolific author. Tom Solomon from the University of Liverpool (UK) was the most cited author. Neurological Sciences and Frontiers in Neurology were the first two most productive journals, while Journal of Neurology held the first in terms of total citations and citations per publication. Cerebrovascular diseases, neurodegenerative diseases, encephalitis and encephalopathy, neuroimmune complications, neurological presentation in children, long COVID and mental health, and telemedicine were the central topics regarding the neurology-related research on COVID-19. Conclusion Neurology-related research on COVID-19 has attracted considerable attention worldwide. Research topics shifted from “morality, autopsy, and telemedicine” in 2020 to various COVID-19-related neurological symptoms in 2021, such as “stroke,” “Alzheimer's disease,” “Parkinson's disease,” “Guillain–Barre syndrome,” “multiple sclerosis,” “seizures in children,” and “long COVID.” “Applications of telemedicine in neurology during COVID-19 pandemic,” “COVID-19-related neurological complications and mechanism,” and “long COVID” require further study.